Hubungan Pemberian Susu Formula dengan Frekuensi Terjadinya ISPA pada Anak Usia 1-3 Tahun - Risti Mariati; Ni Luh Ketut Dewi Aryasari (Indonesian Journal of Health Research, 2018)
Introduction. Acute Respiratory Infections (ARI) still a major couse of disease morbidity and mortality in toodlers. ARI is a common disease with mild to severe manifestations. This study aims to determinate the relations of formula feeding with a frequency occurrence of ARI in children aged 1-3 years in sobo community health center Banyuwangi. Methods. The study design was cross sectional, population in this study were all mothers of children aged 1-3 years who were given formula milk are visiting in Sobo community health center Banyuwangi using 42 maternal samples with Accidental sampling method. Results. test showed values 0,000 < α (0,05) it can be concluded alternative hypothesis accepted and hypothes 0 rejected, it means there is a relationship between formula feeding with a frequency occurance of ARI in children aged 1-3 years in Sobo community health center Banyuwangi. Conclusion. The result of this study can be concluded that the factor causing respiratory infection or ARI is formula feeding, toodlers were are given formula milk will be easier exposed ARI. Sobo community health center Banyuwangi expected to improve public health services, for example by providing health education on the impact of formula feeding.